2022
DOI: 10.3390/bs12070218
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Intention of Authorization via Apps: Personality Traits and Expanded Privacy Calculus Perspectives

Abstract: By integrating the extended privacy calculus theory with the Big Five personality theory, this research proposes and validates a conceptual model in the context of mobile application (App) information authorization. It investigates the implications of each component of privacy costs, privacy advantages, and trust on users’ willingness to authorize their information, and explores how the five personality traits affect App users’ perceived benefits, privacy concern, and trust. Simultaneously, the links between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 95 publications
2
7
0
Order By: Relevance
“…People with neuroticism also tend to understand or interpret situations negatively, as they are likely to recognize dishonesty, which might result from discrepancies in distributing or sharing benefits. Consequently, there is less chance for these people to trust others [28], which correlates with Tang et al [40], who indicated that people with neuroticism had a negative relationship with the trust of consumers who used mobile applications. Based on the above data, the third research hypothesis can be postulated as follows.…”
Section: The Relationship Between Personality and Trustsupporting
confidence: 54%
See 1 more Smart Citation
“…People with neuroticism also tend to understand or interpret situations negatively, as they are likely to recognize dishonesty, which might result from discrepancies in distributing or sharing benefits. Consequently, there is less chance for these people to trust others [28], which correlates with Tang et al [40], who indicated that people with neuroticism had a negative relationship with the trust of consumers who used mobile applications. Based on the above data, the third research hypothesis can be postulated as follows.…”
Section: The Relationship Between Personality and Trustsupporting
confidence: 54%
“…People with agreeableness personality traits are willing to cooperate, warm, friendly, and avoid creating conflicts. Studies by Costa and McCrae [11], Deng et al [41], and Tang et al [40] showed that people who have a high level of friendliness and agreeableness always have a high level of trust with others as those who are friendly and have agreeableness always easily trust and have confidence in others. Based on the data above, the fourth research hypothesis can be posited as follows.…”
Section: The Relationship Between Personality and Trustmentioning
confidence: 99%
“…However, several differences exist between this work and prior studies. First, previous studies showed that the notification used by enterprises to publicly inform customers regarding data collection is a critical factor for customers’ willingness to use the recommended information and obviating their privacy behaviors [ 17 , 23 , 81 , 82 ]. Our study, based on PPM, showed that privacy-related behaviors could occur after the users have been informed about the data collection rules and even after they authorized sharing a part of their data at the beginning of using the apps via the corresponding privacy policies.…”
Section: Discussionmentioning
confidence: 99%
“…As potential predictors of users' intention to utilize PETs, they employed TAM in conjunction with users' personality characteristics, such as conscientiousness, agreeableness, neuroticism, extroversion, and openness to experience. 34 In addition, 33 referred to the 35 internet users' information privacy concerns model, which, unlike TAM, incorporates variables assessing privacy concerns, as well as causes of such concerns, such as trust and perceived risks. By contrast, Namara et al 31 provided some insight into certain nonutilitarian factors that users may have considered before choosing to utilize PETs.…”
Section: Literature Reviewmentioning
confidence: 99%